Fabrication and characterization of hardness and microstructure of large sized Al2014-SiC composite. (2021) - Naveen Kumar, S.; Ravitej, Y.P.; Adarsha, H.; Halemani, Balachandra S.; Ravikumar, R.; Karthik, S.B.; khot, Sachin; Abhinandan, L.; Veeracahri, M.
Abstract: Al-SiC is widely used in structural, aerospace and marine applications. In this paper Hardness and microstructural properties are analysed. Fabrication of composite is done by taking Aluminum 2014 as a matrix and SiC as reinforcement using vortex flow casting method, Four samples are fabricated out of which two samples for Al 2014 grade with out reinforcement and AlSiC respectively. Each samples are tested for hardness and micro structure on the surface and cross sections. Results are calculated and tabulated. It is found that Al-SiC gives better hardness and micro structural property when compared with Aluminum 2014 grade. Reciprocating sliding wear test revealed that the SiC reinforced composite possesses highest coefficient of friction when compared with the base alloy (Al2014).